Oxygen Isotope Equilibrium of the Shallow-Water Benthic Foraminifer Hanzawaia nipponica Asano in Tosa Bay, Southwest Japan - Ikehara, Minoru; Kita, Shigetaka; Kawagata, Shungo (Frontiers in Earth Science, 2021)
Oxygen isotopic compositions (δ18O) of benthic foraminifer tests are widely used for reconstructing paleoceanographic changes, such as global ice volumes during glacial–interglacial cycles. Although deep-sea benthic foraminifers have been well characterized and are considered reliable indicators, little attention has been paid to the geochemistry of shallow-water benthic foraminifers. In this study we evaluated δ18O in the shallow-water benthic foraminifer Hanzawaia nipponica Asano, which lives in surface sediments on continental shelves and upper slopes under the influence of two warm currents, the Kuroshio and Tsushima currents, in the East China Sea, northwest Pacific, and southwestern Japan Sea. To evaluate oxygen isotope equilibrium, we analyzed δ18O of H. nipponica and ambient seawater on the continental shelf in Tosa Bay, southwest Japan. Seawater δ18O and salinity in Tosa Bay are similar to those of surface and subsurface waters in the Kuroshio region in the Okinawa Trough and the northwest Pacific. Vertical profiles of seawater δ18O show no variation with water depth (0–200 m) in Tosa Bay. However, tests of living H. nipponica (as determined by staining with Rose Bengal) and fossil (non-stained) H. nipponica, picked from samples of the top centimeter of seafloor sediment, yielded carbonate δ18O values that clearly increase with water depth, suggesting a temperature-dependent relationship. A comparison of carbonate δ18O values in living H. nipponica and those predicted on the basis of seawater δ18O and annual mean bottom temperature shows that H. nipponica tests are in oxygen isotopic equilibrium with ambient seawater. We determined the linear equations of δ18O–temperature relationship, and the slope of -5.26 (0.19‰ °C-1) for living and -4.50 (0.22‰ °C-1) for the fossil H. nipponica, respectively. The carbon isotopic compositions (δ13C) of H. nipponica also closely match seawater δ13C. Thus, we propose that the carbonate δ18O and δ13C of H. nipponica are useful proxies to reconstruct shallow-water paleoenvironmental changes in the northwest Pacific and its marginal seas.